Leukoreduced whole blood–derived platelets treated with antimicrobial peptides maintain in vitro properties during storage. Issue 6 (12th January 2014) - Bosch‐Marcé, Marta; Seetharaman, Shalini; Kurtz, James; Mohan, Ketha V.K.; Wagner, Stephen J.; Atreya, Chintamani D.
<x xml:space="preserve">Abstract</x> Background Bacterial sepsis is still a complication in patients transfused with stored platelets (PLTs). We have recently demonstrated that selected antimicrobial peptides (AMPs) have bactericidal activity in bacteria‐spiked PLTs. In a subsequent preclinical study, we have also shown that these AMPs do not elicit antibody response in rabbits and treatment of PLTs before transfusion does not affect their in vivo recovery and survival in severe combined immunodeficient mice. Here we have selected two such AMPs, Arg‐Trp (RW) repeats of tri‐ and tetra‐peptides (RW3 and RW4) in combination (i.e., cocktail), and evaluated their effect on the in vitro properties of PLTs. Study Design and Methods Leukoreduced ABO‐ and D‐identical whole blood–derived PLT concentrates were pooled and divided into two 60‐mL aliquots in CLX storage bags. On Day 0, one bag received a peptide cocktail of RW3 plus RW4 at 0.01 mmol/L final concentration (test) and the other bag received only phosphate‐buffered saline (PBS), the AMP solvent (control). The treated PLTs were stored for 7 days at 20 to 24°C. Samples were collected on Days 1, 5, and 7 to evaluate the in vitro properties of PLTs with standard assays. Results In vitro properties of the RW3 plus RW4 cocktail–treated PLTs were similar to those incubated with PBS only. There were no significant differences between the control and test PLTs during the 7‐day storage. Conclusion Leukoreduced whole blood–derived PLTs treated with a mixture of RW3 and RW4 peptides maintain their in vitro properties during 7 days of storage.